Motion words selectively modulate direction discrimination sensitivity for threshold motion - Pavan, Andrea; Skujevskis, Māris; Baggio, Giosuè (Frontiers in Human Neuroscience, 2013)
Can speech selectively modulate the sensitivity of a sensory system so that, in the presence of a suitable linguistic context, the discrimination of certain perceptual features becomes more or less likely? In this study, participants heard upward or downward motion words followed by a single visual field of random dots moving upwards or downwards. The time interval between the onsets of the auditory and the visual stimuli was varied parametrically. Motion direction could be either discriminable (suprathreshold motion) or non-discriminable (threshold motion). Participants had to judge whether the dots were moving upward or downward. Results show a double dissociation between discrimination sensitivity (d’) and reaction times depending on whether vertical motion was above or at threshold. With suprathreshold motion, responses were faster for congruent directions of words and dots, but sensitivity was equal across conditions. With threshold motion, sensitivity was higher for congruent directions of words and dots, but responses were equally fast across conditions. The observed differences in sensitivity and response times were largest when the dots appeared 450 ms after word onset, that is, consistently with electrophysiology, at the time the up/down semantics of the word had become available. These data suggest that word meanings can alter the balance between signal and noise within the visual system and affect the perception of low-level sensory features.